2014
DOI: 10.1186/1476-511x-13-122
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia awareness, treatment, control and influence factors among adults in the Jilin province in China: a cross-sectional study

Abstract: BackgroundIn China, even though the prevalence of dyslipidemia among adults increased yearly and dyslipidemia being an important risk factor for cardiovascular diseases among the Chinese population, however, the awareness, treatment and control of dyslipidemia are at low levels, and only limited studies on the influence factors associated with the awareness, treatment and control dyslipidemia in China have been carried out.MethodsThe analysis was based on a representative sample of 7138 adult subjects aged 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 12 publications
3
52
5
Order By: Relevance
“…21 The results of the present study revealed that almost one third of patients had lipid profile in the last year. This is in line with another study carried out in China.…”
Section: Discussion:-mentioning
confidence: 48%
See 2 more Smart Citations
“…21 The results of the present study revealed that almost one third of patients had lipid profile in the last year. This is in line with another study carried out in China.…”
Section: Discussion:-mentioning
confidence: 48%
“…Numerous recent studies showed that education is positively associated with the awareness of and attitude towards dyslipidemia. 21,[25][26][27][28] Regarding job status, as expected, medical professionals expressed higher significant knowledge of and attitude towards dyslipidemia compared with military persons and businessmen. This may be related to the possibility that militaries and businessmen havingless time to focus on their health, and tend to seek late management of any adverse health condition.…”
Section: Discussion:-mentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, this rate varies by region due to different climatic environments, diets, and lifestyles [13]. The latest data from Jilin Province in northeast China reported that the awareness, treatment, and control rate of dyslipidemia were 11.6, 8.4, and 34.8%, respectively, in 2012 [14]. However, this data did not contain the prevalence rates of dyslipidemia or details regarding the subtypes of lipid disorders (high serum total cholesterol, triglycerides, low-density lipoprotein cholesterol, and low high-density lipoprotein cholesterol).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, awareness and treatment of dyslipidemia is extremely low. [5] The global focus on reducing noncommunicable diseases provides an opportunity for China to take advantage of population-wide strategies to promote cardiovascular health and stop the nearepidemic levels of cardiovascular diseases in the country. The United States and other countries have had success in reducing cardiovascular mortality through patient education and focused campaigns targeting risk factors such as smoking, hyperlipidemia, and hypertension.…”
mentioning
confidence: 99%